1982
DOI: 10.1099/0022-1317-60-1-177
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Paramyxoviruses by Immunoprecipitation

Abstract: SUMMARYUsing the technique of immune precipitation of [35S]methionine-labelled infected cell polypeptides followed by SDS-polyacrylamide gel electrophoresis and autoradiography it has been shown that SV5 and a closely related isolate are both antigenically related to human parainfluenza virus type 2. Limited cross-reactions were also demonstrated between parainfluenza virus types 1 and 3 by this method and the apparent molecular weights of the major structural components of human parainfluenza virus types 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
1

Year Published

1984
1984
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 17 publications
5
38
1
Order By: Relevance
“…3) the overall pattern was very similar and clearly very distinct from that of SV5 (Randall et al, 1987). Thus, in general agreement with other published data on the polypeptides of PF-2 (Goswami & Russell, 1982;Cowley & Barry, 1983), SDS-PAGE analysis showed marked differences in the apparent Mr values of the L, HN, NP and F proteins of SV5 and PF-2, the P and M proteins having similar electrophoretic mobilities. We had previously shown that there was little variation between different human, dog or monkey isolates of SV5 either in terms of the apparent Mr of the virion proteins or in terms of their ability to react with the pool of SV5 MAbs used in this The autoradiogram shown in (a) represents an SDS-PAGE gel exposed for 2 weeks; that shown in (b) was exposed for 10 weeks.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…3) the overall pattern was very similar and clearly very distinct from that of SV5 (Randall et al, 1987). Thus, in general agreement with other published data on the polypeptides of PF-2 (Goswami & Russell, 1982;Cowley & Barry, 1983), SDS-PAGE analysis showed marked differences in the apparent Mr values of the L, HN, NP and F proteins of SV5 and PF-2, the P and M proteins having similar electrophoretic mobilities. We had previously shown that there was little variation between different human, dog or monkey isolates of SV5 either in terms of the apparent Mr of the virion proteins or in terms of their ability to react with the pool of SV5 MAbs used in this The autoradiogram shown in (a) represents an SDS-PAGE gel exposed for 2 weeks; that shown in (b) was exposed for 10 weeks.…”
Section: Discussionsupporting
confidence: 90%
“…The results presented in this paper therefore provide evidence that SV5 and PF-2 are distinct species of viruses and are not as closely related antigenically as has been thought (e.g. Goswami & Russell, 1982). However, sequence analysis is required to determine the exact level of evolutionary relatedness of these two viruses.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Simian virus 5 (SV5) and SV41 were originally isolated from cynomolgus monkey kidney cell cultures (Hull et al, 1958;Miller et al, 1964), and SV5-1ike viruses have been isolated from a number of human sources, including the bone marrow and cerebrospinal fluid of multiple sclerosis patients (Goswami & Russell, 1982;Goswami et al, 1987). Furthermore, about 20~ of individuals in London were shown to be infected with SV5 by serological studies (Goswami et al, 1984).…”
mentioning
confidence: 99%